The Function of Commissive Illocutionary Speech Acts in Anime Ajin - Shofy Nur Aidzatul Izza (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This study aims to describe the function of commissive illocutionary speech acts. Determining this topic was based on a preliminary study conducted on 49 students at Surabaya State University, most of whom did not understand commissive illocutionary. The source of data is obtained from Anime Ajin by Gamon Sakurai, particularly the sentences containing commissive illocutionary utterances. This study employed a descriptive qualitative method. Then the main theory used is Ibrahim (1993:34-34). Based on the results, it found 6 functions of commissive illocutionary speech acts in the 41 data, namely 21 data of the promising function, 1 data of the swearing function, 10 data of the proposing function, 4 data of the offering function, 4 data of the bargaining function, and 1 data of the function declare voluntarily. The promising function is marked with å¿…ãšã€ã™ãã€ç´„æŸã™ã‚‹ã€ã¦ã‚„ã‚‹ã€swearing function is marked with èª“ã†ã€proposing function is marked with ã»ã†ãŒã„ã„ã€ã©ã†ã§ã™ã‹ã€offering function is marked with ã¾ã›ã‚“ã‹ã€ã‚ˆã‹ã£ãŸã‚‰ã€f bargaining function is marked with ã‚®ãƒ–ã‚¢ãƒ³ãƒ‰ãƒ†ã‚¤ã‚¯ã€ä»£ã‚ã‚Šã«, and voluntary function is marked with ã¦ã‚‚ã„ã„. Of the six functions, the promising function is the most dominant. This is due to the background of the film, which tells of the escape and hunting of Ajin, so each character often issues promises of action in the future.